Aramid flame-retardant conveyor belt covering rubber and preparation method thereof

By using isomer fibers and synthetic rubber in the aramid flame retardant conveyor belt cover glue, combined with the refining process, the problem of insufficient tensile and stress fatigue resistance of fabric core conveyor belts is solved, and the service life of the conveyor belt is significantly improved and stability.

CN118994751BActive Publication Date: 2025-01-14XIAN ZHONGZHUANG WEINAN RUBBER PROD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411481118.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Fabric core conveyor belts have shortcomings in tensile resistance and stress fatigue resistance, which leads to microcracks that are prone to microcracks during use, weakening their performance and reducing the service life of the conveyor belt.

Method used

Isomeric fibers are used in aramid flame retardant conveyor belt covering glue, and the infusion treatment of polyacrylonitrile and polyvinylidene fluoride fibers and aqueous sodium thiocyanate treatment were prepared to provide heterogeneous fibers with excellent tensile resistance and stress fatigue resistance. The mechanical properties of the covering rubber are improved through the intensive refining process.

Benefits of technology

It significantly improves the tensile and stress fatigue resistance of the cover glue, extends the service life of the conveyor belt, reduces the generation of microcracks caused by stress concentration, and enhances the stability and toughness of the cover glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of conveyor belt covering rubber, and specifically discloses an aramid flame retardant conveyor belt covering rubber and a preparation method thereof. An aramid flame retardant conveyor belt covering rubber is made of the following raw materials in parts by weight: 100-120 parts of synthetic rubber, 1-3 parts of paraffin, 3-5 parts of antioxidant, 1-3 parts of accelerator, 15-25 parts of rubber reinforcing agent, 3-5 parts of sulfur, 1-3 parts of stearic acid, 4-6 parts of nano zinc oxide, 15-25 parts of heterogeneous fibers, and 10-15 parts of aluminum hydroxide. The aramid flame retardant conveyor belt covering rubber prepared in the present application has the advantages of good tensile strength and stress fatigue resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conveyor belt covering rubber, and more specifically, to an aramid flame retardant conveyor belt covering rubber and a preparation method thereof. Background Art

[0002] In the process of coal mining, the mined coal is often transported to the predetermined location with the help of conveyor belts, and the subsequent transportation and loading of coal also cannot be separated from the help of conveyor belts. The commonly used conveyor belts now mainly include steel cord conveyor belts and fabric core conveyor belts.

[0003] Fabric core conveyor belts have the advantages of light weight, low cost and energy saving during operation because their belt cores are made of nylon, polyester and aramid. However, due to the limitations of the fabric's own performance, fabric core conveyor belts have the disadvantages of poor tensile strength and stress fatigue resistance compared to wire rope conveyor belts. In order to make up for the shortcomings of fabric core conveyor belts, the performance of the conveyor belt fabric core and the conveyor belt covering layer material can be improved. This application overcomes the shortcomings of poor tensile strength and stress fatigue resistance of fabric core conveyor belts by improving the performance of the conveyor belt covering layer material.

[0004] The cover material of the conveyor belt is mainly used to protect the belt core and convey the material. In the actual working process of the conveyor belt, the cover material is affected by the impact force of the falling material, the pressure generated by the weight of the material itself, and the vibration of the equipment during operation. Stress fluctuations are generated inside and gradually accumulate, causing stress fatigue, resulting in micro cracks inside and on the surface of the cover material. The generation of these micro cracks will gradually weaken the performance of the cover material, thereby reducing the overall service life of the conveyor belt. In view of this, in order to ensure that the conveyor belt can maintain stable performance in long-term use, the cover material needs to have good stress fatigue resistance to extend the service life of the conveyor belt.

[0005] The Chinese patent application document with publication number CN104927705A discloses a PVG tear-resistant whole core flame-retardant conveyor belt covering rubber and its preparation method. The raw materials for preparing the covering rubber include: nitrile rubber, antioxidant, zinc oxide, stearic acid, carbon black, sulfur, antimony trioxide, chlorinated paraffin, zinc borate, aluminum hydroxide, decabromodiphenyl ether, ammonium polyphosphate, chlorinated paraffin, accelerator, anti-fatigue agent, short fiber. The short fiber and anti-fatigue agent are added to the rubber material to make the covering rubber have the characteristics of strong impact resistance and good tear resistance. However, the improvement of the impact resistance and fatigue resistance of the covering rubber is relatively weak. Summary of the invention

[0006] In order to further improve the tensile strength and stress fatigue resistance of aramid flame retardant conveyor belt covering rubber, the present application provides an aramid flame retardant conveyor belt covering rubber and a preparation method thereof.

[0007] In a first aspect, the present application provides an aramid flame retardant conveyor belt covering rubber, which adopts the following technical solution:

[0008] An aramid flame-retardant conveyor belt covering rubber is made of the following raw materials in parts by weight: 100-120 parts of synthetic rubber, 1-3 parts of paraffin, 3-5 parts of antioxidant, 1-3 parts of accelerator, 15-25 parts of rubber reinforcing agent, 3-5 parts of sulfur, 1-3 parts of stearic acid, 4-6 parts of nano zinc oxide, 15-25 parts of heterogeneous fibers, and 10-15 parts of aluminum hydroxide;

[0009] The preparation method of the heterogeneous fiber comprises the following steps:

[0010] (1) uniformly mixing polyacrylonitrile, polyvinylidene fluoride and dimethylacetamide to obtain a spinning solution;

[0011] (2) The spinning solution is sprayed into the coagulation liquid through the spinneret to coagulate and form. After forming, it is taken out, washed, and dried to obtain fibers;

[0012] (3) The fibers are soaked in a sodium thiocyanate aqueous solution, and then the soaked fibers are taken out, washed, dried, and crushed to obtain heterogeneous fibers.

[0013] By adopting the above technical solution, heterogeneous fibers are added during the preparation process of the aramid flame-retardant conveyor belt covering rubber. The heterogeneous fibers have a different appearance structure from ordinary fibers, and have a stronger bonding force with other components in the covering rubber, are not easy to slide, and improve the strength and toughness of the covering rubber. Polyvinylidene fluoride has excellent toughness, and polyacrylonitrile has good elasticity. The two are mixed and spun to prepare fibers with good elasticity and toughness. Then, they are soaked to obtain heterogeneous fibers. The fiber's own performance is combined with the surface structure characteristics, so that the heterogeneous fibers have excellent tensile and stress fatigue resistance.

[0014] Preferably, in step (1), the mass ratio of polyacrylonitrile, polyvinylidene fluoride and dimethylacetamide is 1:(1.2-1.4):(11-14).

[0015] By adopting the above technical solution, the prepared fiber has a surface structure that is more compatible with the covering rubber.

[0016] Preferably, in step (2), the coagulation liquid is a dimethyl sulfoxide aqueous solution, and preferably, the mass percentage concentration of the dimethyl sulfoxide aqueous solution is 12%-15%.

[0017] By adopting the above technical scheme, during the coagulation process, dimethylacetamide diffuses into dimethyl sulfoxide, and water diffuses into polyacrylonitrile and polyvinylidene fluoride, thereby promoting the coagulation and molding of the fiber; when the mass percentage concentration of the dimethyl sulfoxide aqueous solution is 12%-15%, the fiber surface can show a micro-casting technology effect, thereby improving the fiber toughness.

[0018] Preferably, in step (2), the spinneret aperture is 0.08-0.12 mm.

[0019] By adopting the above technical solution, under the condition of the same fiber quality, when the spinneret aperture is 0.08-0.12mm, the prepared fiber has a large specific surface area, high strength and good toughness. The large specific surface area of ​​the fiber makes the contact area between the fiber and each component large, and the fiber has a strong stress dispersion ability.

[0020] Preferably, in step (3), the mass percentage concentration of the sodium thiocyanate aqueous solution is 45%-50%.

[0021] By adopting the above technical scheme, the sodium thiocyanate aqueous solution has a good dissolving effect on polyacrylonitrile, and the heterogeneous fibers obtained by immersion have a good surface structure, and the heterogeneous fibers have good tensile and stress fatigue resistance.

[0022] Preferably, in step (3), the fiber is immersed in the sodium thiocyanate aqueous solution for 30-60 seconds.

[0023] By adopting the above technical solution, when the immersion time is 30-60s, an appropriate amount of polyacrylonitrile is dissolved without destroying the internal structure of the fiber, so that the fiber surface is isomerized better, the internal structure of the fiber is complete, and the fiber strength is high.

[0024] Preferably, the length of the fibers after crushing in step (3) is 4-7 mm.

[0025] By adopting the above technical solution, when the fiber length is 4-7mm, the stress absorption and dispersion capabilities are the best, and its good tensile and stress fatigue resistance are fully exerted.

[0026] Preferably, the synthetic rubber consists of component A and component B; preferably, component A is styrene-butadiene rubber, and component B is one of butadiene rubber, chloroprene rubber and nitrile rubber.

[0027] By adopting the above technical scheme, when styrene-butadiene rubber is compounded with one of butadiene rubber, chloroprene rubber and nitrile rubber, the covering rubber has good elasticity and aging resistance, better dimensional stability, stronger bonding force with heterogeneous fibers, heterogeneous fibers are not easy to slide, and the dispersion stability of the heterogeneous fibers in the covering rubber is increased.

[0028] Styrene butadiene rubber, butadiene rubber, chloroprene rubber and nitrile rubber all have certain stress fatigue resistance properties.

[0029] Preferably, the antioxidant is one of antioxidant 2246-S, antioxidant RD and antioxidant SP.

[0030] By adopting the above technical scheme, antioxidant 2246-S, antioxidant RD and antioxidant SP can effectively inhibit the oxidative aging of the covering rubber in an aerobic environment, reduce cracks and performance degradation caused by aging, and thus improve the stress fatigue resistance of the rubber.

[0031] Preferably, the accelerator is one of accelerator DM, accelerator CBS and accelerator TBBS.

[0032] By adopting the above technical solution, accelerator DM, accelerator CBS and accelerator TBBS can make the rubber reach a better cross-linking degree in a shorter time, ensuring that the performance of the vulcanized rubber is stable and has stress fatigue resistance.

[0033] Preferably, the rubber reinforcing agent is two of carbon black, white carbon black and nano calcium carbonate.

[0034] By adopting the above technical solution, carbon black, white carbon black and nano calcium carbonate have smaller particle size and higher specific surface area, are evenly dispersed in the covering rubber, and have higher strength themselves, which can improve the covering rubber's resistance to stress.

[0035] In a second aspect, the present application provides a method for preparing an aramid flame retardant conveyor belt covering rubber, comprising the following steps:

[0036] S1: One-stage mixing: Put the synthetic rubber into an internal mixer, mix it, then add stearic acid, nano zinc oxide, paraffin, antioxidant, accelerator, mix it, then add rubber reinforcing agent, heterogeneous fiber, aluminum hydroxide, mix it, and produce sheets according to the thickness of 7-9mm. Cool it to get a first-stage mixed rubber.

[0037] S2: Two-stage mixing: put the first-stage mixed rubber into an internal mixer, then add sulfur, mix it, and produce sheets according to the thickness of the rubber 7-9mm. After cooling, the aramid flame-retardant conveyor belt covering rubber is obtained.

[0038] Preferably, in step S1, the banburying pressure is not less than 0.5 MPa, the banburying temperature is 110-140° C., the banburying time is 8-12 min, and the rotor speed of the banbury mixer is 30-40 rpm.

[0039] By adopting the above technical solution and appropriate mixing process parameters, the raw materials can be mixed evenly, which makes it easier for the covering rubber to quickly disperse stress when it is impacted by external forces and has good mechanical properties.

[0040] Preferably, in step S2, the banburying pressure is not less than 0.5 MPa, the banburying temperature is 100-110° C., the banburying time is 8-12 min, and the rotor speed of the banbury mixer is 20-30 rpm.

[0041] By adopting the above technical solution and appropriate vulcanization process parameters, the rubber can be vulcanized quickly and evenly, which is conducive to the formation of a uniform cross-linked network structure of the rubber, facilitates the rapid dispersion of stress when the covering rubber is impacted by external force, and has good mechanical properties.

[0042] Preferably, in step S1 and step S2, the thickness of the output sheet is 7-9 mm.

[0043] By adopting the above technical solution, the covering glue can have sufficient strength to resist external forces while maintaining a certain flexibility. It can better absorb and disperse stress when subjected to repeated stress, making the covering glue less likely to break and damage during use, thereby increasing the service life of the covering glue.

[0044] In summary, this application has the following beneficial effects:

[0045] 1. The present application adopts heterogeneous fibers as an auxiliary agent for improving the mechanical properties of the covering adhesive. Polyacrylonitrile is soluble in an aqueous solution of sodium thiocyanate, while polyvinylidene fluoride is insoluble in an aqueous solution of sodium thiocyanate. By immersing the polyacrylonitrile-polyvinylidene fluoride fiber in an aqueous solution of sodium thiocyanate, the polyacrylonitrile on the fiber surface can be dissolved, so that the surface of the polyacrylonitrile-polyvinylidene fluoride fiber can be isomerized and fiberized. When the heterogeneous fiber is bent, thanks to the presence of serrated protrusions on the surface, the stress is dispersed more evenly, avoiding breakage caused by local stress concentration, so that the heterogeneous fiber has the performance of being folded multiple times without breaking.

[0046] 2. When the covering rubber is impacted, stress concentration will occur inside, resulting in micro cracks inside and reducing the mechanical properties of the covering rubber. After the heterogeneous fibers are added, their excellent stress dispersion ability is utilized to evenly disperse the concentrated stress inside the covering rubber, reduce the generation of internal micro cracks, and make the covering rubber have the characteristics of stress fatigue resistance.

[0047] 3. The non-smooth structure of the heterogeneous fiber surface increases its specific surface area, allowing the heterogeneous fiber to contact with other components in the covering glue more fully, enhancing the bonding force, and increasing the compatibility of the heterogeneous fiber in the covering glue. At the same time, the heterogeneous fiber is not easy to slide when the covering glue is subjected to force, which makes the covering glue more stable. DETAILED DESCRIPTION

[0048] The present application is further described in detail below with reference to the embodiments.

[0049] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0050] Example 1

[0051] The aramid flame retardant conveyor belt covering rubber of this embodiment is made of the following raw materials: 1365g of styrene-butadiene rubber, 585g of butadiene rubber, 19.5g of paraffin, 58.5g of antioxidant 2246-S, 19.5g of accelerator DM, 190.5g of carbon black, 102g of white carbon black, 58.5g of sulfur, 19.5g of stearic acid, 78g of nano zinc oxide, 292.5g of heterogeneous fibers, and 195g of aluminum hydroxide.

[0052] The preparation method of the heterogeneous fibers of this embodiment is as follows:

[0053] Take 10g of polyacrylonitrile, 12g of polyvinylidene fluoride, and 110g of dimethylacetamide and put them into a three-necked flask, heat to 60℃ and stir to dissolve, then vacuum degas, put it into the barrel of a wet spinning machine, and press it into a 12% dimethyl sulfoxide aqueous solution through a spinneret with an aperture of 0.08mm to coagulate and form. Rinse the formed fiber with deionized water, dry it, and then soak it in a 45% sodium thiocyanate aqueous solution for 60s. After the soaking, rinse it with deionized water, dry it, and crush it into a state with a length of 4mm to obtain heterogeneous fibers.

[0054] The steps for preparing the aramid flame retardant conveyor belt covering rubber of this embodiment are as follows:

[0055] S1: One-stage mixing: 1365g of styrene-butadiene rubber and 585g of cis-1,2-dimethylformamide were added to an internal mixer, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 110°C, the internal mixer rotor speed was 40 rpm, and the internal mixing was performed for 12min; then 19.5g of stearic acid, 78g of nano zinc oxide, 19.5g of paraffin wax, 58.5g of antioxidant 2246-S, and 19.5g of accelerator DM were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 30 rpm, and the internal mixing was performed for 10min; then 190.5g of carbon black, 102g of white carbon black, 292.5g of heterogeneous fibers, and 195g of aluminum hydroxide were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 120°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was performed for 8min. The rubber was sheeted according to a thickness of 7mm, and cooled for 8h to obtain a one-stage mixed rubber.

[0056] S2: Second stage mixing: put the first stage mixed rubber into an internal mixer, and then add 58.5g of sulfur, the internal mixing pressure is 0.6MPa, the internal mixing temperature is 100℃, the internal mixer rotor speed is 20 rpm, the internal mixing is 12min, the rubber is cut into sheets with a thickness of 7mm, and cooled to obtain the aramid flame retardant conveyor belt covering rubber.

[0057] Example 2

[0058] The aramid flame retardant conveyor belt covering rubber of this embodiment is made of the following raw materials: 1530g of styrene-butadiene rubber, 510g of chloroprene rubber, 51g of paraffin, 85g of antioxidant SP, 51g of accelerator CBS, 255g of carbon black, 170g of nano calcium carbonate, 85g of sulfur, 51g of stearic acid, 102g of nano zinc oxide, 425g of heterogeneous fiber, and 255g of aluminum hydroxide.

[0059] The preparation method of the heterogeneous fibers of this embodiment is as follows:

[0060] Take 20g of polyacrylonitrile, 28g of polyvinylidene fluoride, and 280g of dimethylacetamide and put them into a three-necked flask, heat to 60℃ and stir to dissolve, then vacuum degas, put it into the barrel of a wet spinning machine, and press it into a 15% dimethyl sulfoxide aqueous solution through a spinneret with a pore size of 0.12mm to coagulate and form. Rinse the formed fiber with deionized water, dry it, and then soak it in a 50% sodium thiocyanate aqueous solution for 30s. After the soaking, rinse it with deionized water, dry it, and crush it into a state with a length of 7mm to obtain heterogeneous fibers.

[0061] The steps for preparing the aramid flame retardant conveyor belt covering rubber of this embodiment are as follows:

[0062] S1: One-stage mixing: 1530g of styrene-butadiene rubber and 510g of chloroprene rubber were added to an internal mixer, the internal mixing pressure was 0.5MPa, the internal mixing temperature was 140°C, the internal mixer rotor speed was 30 rpm, and the internal mixing was 8min; then 51g of stearic acid, 102g of nano zinc oxide, 51g of paraffin, 85g of antioxidant SP, and 51g of accelerator CBS were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 10min; then 255g of carbon black, 170g of nano calcium carbonate, 425g of heterogeneous fibers, and 255g of aluminum hydroxide were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 110°C, the internal mixer rotor speed was 40 rpm, and the internal mixing was 12min. The rubber was sheeted according to a thickness of 9mm and cooled for 8h to obtain a first-stage mixed rubber.

[0063] S2: Second stage mixing: put the first stage mixed rubber into an internal mixer, and then add 85g of sulfur, the internal mixing pressure is 0.5MPa, the internal mixing temperature is 110℃, the internal mixer rotor speed is 30 rpm, the internal mixing is 8min, the rubber is cut into sheets with a thickness of 9mm, and cooled to obtain the aramid flame retardant conveyor belt covering rubber.

[0064] Example 3

[0065] The aramid flame retardant conveyor belt covering rubber of this embodiment is made of the following raw materials: 1326g of styrene-butadiene rubber, 459g of nitrile rubber, 34g of paraffin, 68g of antioxidant RD, 34g of accelerator TBBS, 255g of white carbon black, 85g of nano calcium carbonate, 68g of sulfur, 34g of stearic acid, 102g of nano zinc oxide, 340g of heterogeneous fiber, and 204g of aluminum hydroxide.

[0066] The preparation method of the heterogeneous fibers of this embodiment is as follows:

[0067] Take 13g of polyacrylonitrile, 15.6g of polyvinylidene fluoride, and 170g of dimethylacetamide and put them into a three-necked flask, heat to 60℃ and stir to dissolve, then vacuum degas, put it into the barrel of a wet spinning machine, and press it into a 13% dimethyl sulfoxide aqueous solution through a spinneret with an aperture of 0.12mm to coagulate and form. Rinse the formed fiber with deionized water, dry it, and then soak it in a 48% sodium thiocyanate aqueous solution for 30s. After the soaking, rinse it with deionized water, dry it, and crush it into a state with a length of 5mm to obtain heterogeneous fibers.

[0068] The steps for preparing the aramid flame retardant conveyor belt covering rubber of this embodiment are as follows:

[0069] S1: One-stage mixing: 1326g of styrene-butadiene rubber and 459g of nitrile rubber were added to an internal mixer, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 120°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 8min; then 34g of stearic acid, 102g of nano zinc oxide, 34g of paraffin, 68g of antioxidant RD, and 34g of accelerator TBBS were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 10min; then 255g of white carbon black, 85g of nano calcium carbonate, 340g of heterogeneous fibers, and 204g of aluminum hydroxide were added, the internal mixing pressure was 0.5MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 10min. The rubber was sheeted according to a thickness of 8mm and cooled for 8h to obtain a first-stage mixed rubber.

[0070] S2: Second stage mixing: put the first stage mixed rubber into an internal mixer, and then add 68g of sulfur, the internal mixing pressure is 0.6MPa, the internal mixing temperature is 100℃, the internal mixer rotor speed is 20 rpm, the internal mixing is 8min, the rubber is cut into sheets with a thickness of 8mm, and cooled to obtain the aramid flame retardant conveyor belt covering rubber.

[0071] Comparative Example 1

[0072] The aramid flame retardant conveyor belt covering rubber of this comparative example is made of the following raw materials: 1330g of styrene-butadiene rubber, 460g of nitrile rubber, 34g of paraffin, 68g of antioxidant RD, 34g of accelerator TBBS, 255g of white carbon black, 85g of nano calcium carbonate, 68g of sulfur, 34g of stearic acid, 102g of nano zinc oxide, 340g of polyacrylonitrile isomerized fiber, and 204g of aluminum hydroxide.

[0073] The preparation method of the polyacrylonitrile isomerized fiber of this comparative example is as follows:

[0074] Take 35g of polyacrylonitrile and 200g of dimethylacetamide and put them into a three-necked flask, heat to 60℃ and stir to dissolve, then vacuum degas, put it into the barrel of a wet spinning machine, and press it into a 13% dimethyl sulfoxide aqueous solution through a spinneret with an aperture of 0.12mm to coagulate and form. Rinse the formed fiber with deionized water, dry it, and then soak it in a 48% sodium thiocyanate aqueous solution for 30s. After the soaking, rinse it with deionized water, dry it, and crush it into a state with a length of 5mm to obtain polyacrylonitrile isomerized fiber.

[0075] The preparation steps of the aramid flame retardant conveyor belt covering rubber of this comparative example are as follows:

[0076] S1: One-stage mixing: 1330g of styrene-butadiene rubber and 460g of nitrile rubber were added to an internal mixer, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 120°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 8min; then 34g of stearic acid, 102g of nano zinc oxide, 34g of paraffin, 68g of antioxidant RD, and 34g of accelerator TBBS were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 10min; then 255g of white carbon black, 85g of nano calcium carbonate, 340g of polyacrylonitrile isomerized fiber, and 204g of aluminum hydroxide were added, the internal mixing pressure was 0.5MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was 10min. The rubber was sheeted according to the thickness of 8mm, and cooled for 8h to obtain a one-stage mixed rubber.

[0077] S2: Second stage mixing: put the first stage mixed rubber into an internal mixer, and then add 68g of sulfur, the internal mixing pressure is 0.6MPa, the internal mixing temperature is 100℃, the internal mixer rotor speed is 20 rpm, the internal mixing is 8min, the rubber is cut into sheets with a thickness of 8mm, and cooled to obtain the aramid flame retardant conveyor belt covering rubber.

[0078] Comparative Example 2

[0079] The aramid flame retardant conveyor belt covering rubber of this comparative example is made of the following raw materials: 1365g of styrene-butadiene rubber, 585g of butadiene rubber, 19.5g of paraffin, 58.5g of antioxidant 2246-S, 19.5g of accelerator DM, 190.5g of carbon black, 102g of white carbon black, 58.5g of sulfur, 19.5g of stearic acid, 78g of nano zinc oxide, 292.5g of glass fiber, and 195g of aluminum hydroxide.

[0080] The preparation steps of the aramid flame retardant conveyor belt covering rubber of this comparative example are as follows:

[0081] S1: One-stage mixing: 1365g of styrene-butadiene rubber and 585g of cis-1,2-dimethylformamide were added to an internal mixer, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 110°C, the internal mixer rotor speed was 40 rpm, and the internal mixing was performed for 12min; then 19.5g of stearic acid, 78g of nano zinc oxide, 19.5g of paraffin wax, 58.5g of antioxidant 2246-S, and 19.5g of accelerator DM were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 130°C, the internal mixer rotor speed was 30 rpm, and the internal mixing was performed for 10min; then 190.5g of carbon black, 102g of white carbon black, 292.5g of glass fiber, and 195g of aluminum hydroxide were added, the internal mixing pressure was 0.6MPa, the internal mixing temperature was 120°C, the internal mixer rotor speed was 35 rpm, and the internal mixing was performed for 8min. The rubber was sheeted according to a thickness of 7mm, and cooled for 8h to obtain a first-stage mixed rubber.

[0082] S2: Second stage mixing: put the first stage mixed rubber into an internal mixer, and then add 58.5g of sulfur, the internal mixing pressure is 0.6MPa, the internal mixing temperature is 100℃, the internal mixer rotor speed is 20 rpm, the internal mixing is 12min, the rubber is cut into sheets with a thickness of 7mm, and cooled to obtain the aramid flame retardant conveyor belt covering rubber.

[0083] Performance testing

[0084] The performance testing method of aramid flame retardant conveyor belt covering rubber is as follows:

[0085] 1. Tensile stress-strain performance test

[0086] The mechanical properties test method of the aramid flame retardant conveyor belt cover rubber refers to the national standard GB / T528-2009 and is measured by the high and low temperature tensile testing machine model HZ-1003C produced by Dongguan Lixian Instrument Technology Co., Ltd. The cover rubber is made into a dumbbell shape, the test temperature is 25℃, and the speed is 500mm / min.

[0087] 2. Tension fatigue test

[0088] The tensile fatigue test method of the aramid flame retardant conveyor belt cover rubber refers to the national standard GB / T1688-2008 and is measured by the rubber tensile fatigue testing machine model XHPL-2000N produced by Jinan Xinghuo Testing Machine Co., Ltd.; test parameters: elongation is 100% and frequency is 5Hz.

[0089] The performance test data of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are shown in Table 1 below:

[0090] Table 1 Test data

[0091]

[0092] From the analysis of Examples 1-3, Comparative Examples 1 and 2 and in combination with Table 1, it can be seen that the addition of heterogeneous fibers in the aramid flame retardant conveyor belt covering rubber can significantly improve its tensile strength, elongation at break and tensile fatigue life, indicating that the aramid flame retardant conveyor belt covering rubber has good tensile resistance and stress fatigue resistance.

[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A flame retardant aramid conveyor belt covering rubber, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100-120 parts of synthetic rubber, 1-3 parts of paraffin wax, 3-5 parts of antioxidant, 1-3 parts of accelerator, 15-25 parts of rubber reinforcing agent, 3-5 parts of sulfur, 1-3 parts of stearic acid, 4-6 parts of nano zinc oxide, 15-25 parts of heterogeneous fiber and 10-15 parts of aluminum hydroxide; The preparation method of the heterogeneous fiber comprises the following steps: (1) uniformly mixing polyacrylonitrile, polyvinylidene fluoride and dimethylacetamide to obtain a spinning solution; (2) The spinning solution is sprayed into the coagulation liquid through the spinneret to coagulate and form. After forming, it is taken out, washed, and dried to obtain fibers; (3) The fibers are soaked in a sodium thiocyanate aqueous solution, and then the soaked fibers are taken out, washed, dried, and crushed to obtain heterogeneous fibers.

2. The aramid flame retardant conveyor belt covering rubber according to claim 1, characterized in that: In the step (1), the mass ratio of polyacrylonitrile, polyvinylidene fluoride and dimethylacetamide is 1:(1.2-1.4):(11-14).

3. The aramid flame retardant conveyor belt covering rubber according to claim 1, characterized in that: In the step (2), the coagulation liquid is a dimethyl sulfoxide aqueous solution; the mass percentage concentration of the dimethyl sulfoxide aqueous solution is 12%-15%.

4. The aramid flame retardant conveyor belt covering rubber according to claim 1, characterized in that: In the step (3), the mass percentage concentration of the sodium thiocyanate aqueous solution is 45%-50%.

5. The aramid flame retardant conveyor belt covering rubber according to claim 1, characterized in that: In the step (3), the fiber is immersed in the sodium thiocyanate aqueous solution for 30-60 seconds.

6. The aramid flame retardant conveyor belt covering rubber according to claim 1, characterized in that: The synthetic rubber consists of component A and component B; component A is styrene-butadiene rubber; and component B is one of butadiene rubber, chloroprene rubber and nitrile rubber.

7. A method for preparing the aramid flame retardant conveyor belt covering rubber as claimed in claim 1, characterized in that: The steps include: S1: One-stage mixing: Put the synthetic rubber into an internal mixer, mix it, then add stearic acid, nano zinc oxide, paraffin, antioxidant, accelerator, mix it, then add rubber reinforcing agent, heterogeneous fiber, aluminum hydroxide, mix it, produce sheets, cool it, and obtain a first-stage mixed rubber; S2: Two-stage mixing: put the first-stage mixed rubber into an internal mixer, then add sulfur, internally mix, produce sheets, cool, and obtain aramid flame retardant conveyor belt covering rubber.

8. The method for preparing an aramid flame retardant conveyor belt covering rubber according to claim 7, characterized in that: The thickness of the sheets produced in step S1 and step S2 is 7-9 mm.

Citation Information

Patent Citations

  • PVG anti-tear whole core flame retardant conveyor belt cover rubber and preparation method thereof

    CN104927705A

  • Superfine aramid fiber as well as preparation method and application thereof

    CN115044996A

  • Glass fiber cloth and preparation method thereof

    CN118125728A